2022
DOI: 10.1007/s12015-022-10370-8
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres and Mitochondrial Metabolism: Implications for Cellular Senescence and Age-related Diseases

Abstract: Cellular senescence is an irreversible cell arrest process, which is determined by a variety of complicated mechanisms, including telomere attrition, mitochondrial dysfunction, metabolic disorders, loss of protein homeostasis, epigenetic changes, etc. Cellular senescence is causally related to the occurrence and development of age-related disease. The elderly is liable to suffer from disorders such as neurodegenerative diseases, cancer, and diabetes. Therefore, it is increasingly imperative to explore specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 107 publications
1
46
0
Order By: Relevance
“…When the DNA damage response (DDR) is prolonged, it promotes senescence [4]. Further known mechanisms underlying senescence are: (1) persistent DDR activation at telomeres, the ends of chromosomes, which is sufficient to activate replicative cell senescence [8]; (2) oncogene activation partly via reactive oxygen species (ROS) production, determining hyperproliferation and altered DNA replication profiles [4,8]; (3) cell cycle arrest by upregulation of p21 and p16 [9]; (4) mitochondrial abnormalities with an increase in ROS synthesis and impairment in biogenesis and mitophagy [10]; (5) induction to resistance to apoptosis by upregulation of the antiapoptotic proteins [10]; (6) metabolic changes determined by senescence-associated-β-galactosidase (SA-β gal) accumulation along with the increase in cellular lysosomal content [10]; (7) large-scale chromatin reorganization occurring with the generation of senescence-associated heterochromatin foci, which suppress transcription of pro-proliferation genes [10]; (8) secretion of pro-inflammatory cytokines, chemokines, proteases, and growth factors that influence the neighbouring cells (SASP profile); (9) morphological alterations including cellular flattening and enlargement [10]; (10) post-transcriptional regulatory pathways taking place at different levels: through the action of mRNA-binding proteins (RBPs) and noncoding RNAs [11][12][13][14]; through a dysregulated splicing factor expression [12,15]; and through N6-methyladenosine (m6A) processes with specific m6A-binding proteins [14].…”
Section: Introductionmentioning
confidence: 99%
“…When the DNA damage response (DDR) is prolonged, it promotes senescence [4]. Further known mechanisms underlying senescence are: (1) persistent DDR activation at telomeres, the ends of chromosomes, which is sufficient to activate replicative cell senescence [8]; (2) oncogene activation partly via reactive oxygen species (ROS) production, determining hyperproliferation and altered DNA replication profiles [4,8]; (3) cell cycle arrest by upregulation of p21 and p16 [9]; (4) mitochondrial abnormalities with an increase in ROS synthesis and impairment in biogenesis and mitophagy [10]; (5) induction to resistance to apoptosis by upregulation of the antiapoptotic proteins [10]; (6) metabolic changes determined by senescence-associated-β-galactosidase (SA-β gal) accumulation along with the increase in cellular lysosomal content [10]; (7) large-scale chromatin reorganization occurring with the generation of senescence-associated heterochromatin foci, which suppress transcription of pro-proliferation genes [10]; (8) secretion of pro-inflammatory cytokines, chemokines, proteases, and growth factors that influence the neighbouring cells (SASP profile); (9) morphological alterations including cellular flattening and enlargement [10]; (10) post-transcriptional regulatory pathways taking place at different levels: through the action of mRNA-binding proteins (RBPs) and noncoding RNAs [11][12][13][14]; through a dysregulated splicing factor expression [12,15]; and through N6-methyladenosine (m6A) processes with specific m6A-binding proteins [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, telomere shortening occurs in each DNA replication. This is due to DNA polymerase’s inability to replicate the region where the primers are placed on the DNA template, leading to cellular senescence or apoptosis [ 4 ]. A previous study has demonstrated that chronic inflammation can exacerbate telomere dysfunction by increasing reactive oxygen species (ROS)-mediated DNA damage and thus accelerate the accumulation of senescent cells in mice [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggests that such association between telomeres and mitochondria may have been present but not yet fully recognized. According to this recent study, telomeres control overall metabolic performance by acting through p53 ( 96 ). Making such a connection appears to have brought the mitochondria and the nucleus closer together and help elucidating the fundamental reasons of aging.…”
Section: Mitophagy and Telomeresmentioning
confidence: 99%